THE INFLUENCE OF WORK DISCIPLINE, PHYSICAL WORK ENVIRONMENT AND CAREER DEVELOPMENT ON AFFECTIVE COMMITMENT WITH EXTRINSIC MOTIVATION AS AN INTERVENING VARIABLE IN THE DEPARTMENT OF LABOR AND SPECIAL REGION TRANSMIGRATION YOGYAKARTA - Irfan Bimantoro; Prayeti; Gendro Wiyono (International Journal of Accounting, Management, Economics and Social Sciences (IJAMESC), 2024)
This research aims to analyze the influence of work discipline, physical work environment and career development on affective commitment with extrinsic motivation as an intervening variable in the Yogyakarta Special Region Manpower and Transmigration Service. The subjects and objects in this research were all employees at the Yogyakarta Special Region Manpower and Transmigration Service, namely 100 respondents. This type of research uses quantitative techniques and data processing techniques in research using SmartPLS 3.3.3. Work Discipline Has No Effect on Extrinsic Motivation with a Parameter Coefficient (Original Sample) of 0.095, with a t-statistic value of 1.347 and a p-value of 0.179. With a p-value > 0.05. The physical work environment has a significant effect on Extrinsic Motivation, having a Parameter Coefficient (Original Sample) of 0.501 with a t-statistic value of 5.684 and a p-value of 0.000. With a p-value < 0.05. Career Development has a significant effect on Extrinsic Motivation. Has a Parameter Coefficient (Original Sample) of 0.368 with a t-statistic value of 4.373 and a p-value of 0.000<0.05. Work Discipline has a significant effect on Affective Commitment having a Parameter Coefficient (Original Sample) of 0.305, with a t-statistic value of 2.956 and a p-value of 0.003<0.05. Career Development has no effect on Affective Commitment having a Parameter Coefficient (Original Sample) of 0.255 with a t-statistical value of 1.909 and a p-value of 0.057>0.05. Extrinsic Motivation (Y2) has no effect on Affective Commitment, having a Parameter Coefficient (Original Sample) of 0.187 with a t-statistical value of 1.166 and a p-value of 0.244> 0.05.